PERAN KEPALA MADRASAH DALAM PELAKSANAAN MANAJEMEN PESERTA DIDIK DI MI NURUL YAQIN BULULAWANG MALANG - Aulatun Nahdiyatid Diniyah (STAI Ma'had Aly Al-Hikam Malang, 2020)
The main objective of educational institutions is the output of their students. Therefore it requires good student management as well as the role of the principal in running and managing it. This research uses a descriptive research method with a qualitative approach. The purpose of this research is to describe in real terms the implementation of student management and to know the role of the principal in the management of students at MI Nurul Yaqin Bululawang Malang. Data collection techniques include: observation, interviews and documentation. The research subjects were school principals, student staff, teachers, PPDB committee heads, students and alumni of MI Nurul Yaqin Bululawang Malang. The results showed that: 1) the implementation of student management at MI Nurul Yaqin Bululawang Malang was quite good. This is evidenced by implementing the stages of student management properly even though there are some that have not been implemented. 2) the role of the head of the madrasah in the implementation of student management has been carried out properly in accordance with its role as educator, manager, administrator, supervisor, leader, innovator and motivator.